2020
DOI: 10.1093/jb/mvaa133
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic actin-dependent nucleoskeleton and cell identity

Abstract: Actin is an essential regulator of cellular functions. In the eukaryotic cell nucleus, actin regulates chromatin as a bona fide component of chromatin remodeling complexes, it associates with nuclear RNA polymerases to regulate transcription and is involved in co-transcriptional assembly of nascent RNAs into ribonucleoprotein complexes. Actin dynamics are therefore emerging as a major regulatory factor affecting diverse cellular processes. Importantly, the involvement of actin dynamics in nuclear functions is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 159 publications
0
16
0
Order By: Relevance
“…Actin is mainly located at the cell membrane, but also at specific mitochondrial subpopulations (Venit et al, 2021). Interactions between mitochondria and the actin cytoskeleton link the essential functions of this organelle to a plethora of cellular physiological processes.…”
Section: Actin Cytoskeleton Involvement On Mitochondrial Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actin is mainly located at the cell membrane, but also at specific mitochondrial subpopulations (Venit et al, 2021). Interactions between mitochondria and the actin cytoskeleton link the essential functions of this organelle to a plethora of cellular physiological processes.…”
Section: Actin Cytoskeleton Involvement On Mitochondrial Functionmentioning
confidence: 99%
“…In yeast, the ERMES complex regulates the stability and organization of mtDNA in nucleoids in an actin-dependent manner (Boldogh and Pon, 2006); in mammals, MERCs are spatially-linked to mitochondrial nucleoids, regulating their distribution, division and active transportation by the microtubules (Lewis et al, 2016). Although the presence of actin inside mitochondria and its functional connection with mtDNA was debated for decades (Venit et al, 2021), recent super-resolution microscopy-based studies probed the presence of β-actin-containing structures inside the mitochondrial matrix (Dadsena et al, 2021). Moreover, human cells lacking β-actin showed higher sensitivity to stress caused by loss of mitochondrial membrane potential (ΔΨ) plus perturbed mtDNA mass and nucleoid organization (Xie et al, 2018), suggesting a regulatory role in mtDNA transcription and quality control.…”
Section: Actin Cytoskeleton On Mtdna Expression and Maintenancementioning
confidence: 99%
“…As previously discussed HDAC6 modulates actin stability ( Zhang et al, 2007 ). Actin is not only important for mitochondrial motility along with microtubules, but actin, particularly β-actin, may also play a role in mitochondrial gene expression ( Moore and Holzbaur, 2018 ; Reyes et al, 2011 ; Venit et al, 2021 ). Cortactin, when hypoacetylated, can lead to actin instability and thus may alter mitochondrial motility and function ( Zhang et al, 2007 ).…”
Section: Hdac6 and Mitochondrial Dysfunction In Peripheral Neuropathymentioning
confidence: 99%
“…For many years, the location of actin was open to debate since actin did not present a nuclear localization sequence and, therefore, presence in this organelle was assigned to cytosolic contamination caused due to its high expression levels. Many subsequent studies confirmed that the presence of actin in the nucleus was indeed real and that it even had a very relevant role in transcription and transcriptional regulation through a sophisticated mechanism in eukaryotic cells (for a review see [ 69 ]). Cells can reach a high level of gene expression regulation by tuning the state and levels of actin.…”
Section: New Functions For Cofilin In Neurodegenerative Diseasesmentioning
confidence: 99%